Isolation and structural characterization of a titanacyclopropane as key intermediate in the double aryl Grignard addition to 2-(arylethynyl)pyridine derivatives - Foschi, Francesco; Roth, Torsten; Enders, Markus; Wadepohl, Hubert; Clot, Eric; Gade, Lutz H. (Chemical communications, 2018)
A titanacyclopropane species, which is a key reaction intermediate in the Ti(OiPr)4-mediated double aryl Grignard addition to 1,2-di(pyridin-2-yl)ethyne and related alkynes, was isolated and fully characterized. Based on this observation a one-pot synthesis of diarylated 1,2-di(pyridin-2-yl)ethanes and 2-(1,2,2-triarylvinyl)-pyridines was developed, including the tetraarylation of V-shaped 2,6-bis(arylethynyl)pyridines.
Gesehen am 03.04.2020